THINGS I HAVE LEARNED (SO FAR) - Cohen, Jacob (Anales de Psicología / Annals of Psychology)
This is an account of what I have learned (so far) about the application of statics to psychology and the other sociobiomedical sciences. It includes the principles “less is more” (fewer variables, more highly targeted issues, sharp rounding off), “simple is better” (graphic representation, unit weighting for linear composites), and “some things you learn aren’t so”. I have learned to avoid the many misconceptions that surround Fisherian null hypothesis testing. I have also learned the importance of power analysis and the determination of just how big (rather than how statistically significant) are teh effects that we study. Finally, I have learned taht there is no royal road to statistical induction, that the informed judgement of the investigator is the cruical element in the interpretation of data, and that things take time.